Pericardial obliteration by angiosarcoma. Issue 3 (September 1988) - Cheesman, M G; Webster, J; Rowlands, D
Abstract : Primary cardiac angiosarcoma caused pericardial obliteration and death from tamponade in a 66 year old man.